Water Extract of Mentha arvensis L. Attenuates Estrogen Deficiency-Induced Bone Loss by Inhibiting Osteoclast Differentiation - Jang, Seon-A; Hwang, Youn-Hwan; Yang, Hyun; Ryuk, Jin Ah; Kim, Taesoo; Ha, Hyunil (Frontiers in Pharmacology, 2021)
Mentha arvensis L., is an aromatic herb that belongs to the Lamiaceae family and widely used as medicinal applications, essential oil applications, and food flavoring. The extract of M. arvensis has been reported to exert sedative-hypnotic, anti-inflammatory, anti-fungal, and anti-bacterial effects. However, its effects on bone metabolism have not yet been studied. Here, we investigated the effects of the water extract of M. arvensis (WEMA) on osteoclast formation in vitro and bone loss in an ovariectomized mouse model. We found that WEMA inhibited osteoclast differentiation by directly acting on osteoclast precursor cells. The WEMA inhibited receptor activator of nuclear factor-κB ligand (RANKL)-induced the expression of c-Fos and NFATc1, crucial transcription factors for osteoclast differentiation, by suppressing RANKL-induced activation of early signaling pathways such as those of MAPKs and NF-κB. In addition, oral administration of WEMA suppressed ovariectomy-induced trabecular bone loss in mice. We additionally identified phytochemicals in WEMA that are known to have anti-osteoclastogenic or anti-osteoporotic properties. Collectively, these results suggest that WEMA is a promising herbal candidate that can be used to prevent or treat postmenopausal osteoporosis.